The Influence of Clean and Healthy Living Parenting and Home Environmental Health Conditions on Toddler Health Status - Ahmad Khadavi; Dwi Hastuti (Journal of Child, Family, and Consumer Studies, 2025)
Clean and healthy parenting practices are essential for maintaining a healthy home environment and stabilizing children's health. This study aimed to analyze the influence of clean and healthy parenting, as well as home environmental conditions, on the health status of toddlers. A quantitative approach with a cross-sectional design and purposive sampling was used. The respondents were mothers with toddlers in Palabuhanratu Subdistrict. The findings showed that while clean and healthy parenting was generally adequate, most home environments and children's health conditions still need improvement. Issues such as water cleanliness, sanitation, and limited household facilities contribute to an unhealthy living environment, which negatively affects child health. Various illnesses were observed among the children, with skin rashes being the most common and persistent. Other illnesses included influenza, diarrhea, dengue fever, vomiting, colds, and asthma, though these were less frequent. Overall, the study found a significant positive relationship between clean and healthy parenting, environmental conditions, and toddler health status